European Union data protection and external trade: Having the best of both worlds? - Annegret Bendiek; Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2016)
The trade in digital technology and services has become an absolutely central element of international economic relations. A substantial part of this trade is associated with the transfer of data, some of it personal, and many of the new products and services emerging in connection with the internet exhibit new characteristics of relevance for data protection. A significant need for regulation has thus arisen, requiring closer cooperation between experts for trade law, data protection, and information and communication technology (ICT). This applies above all to the current negotiations on the Transatlantic Trade and Investment Partnership (TTIP) and to the new agreement on transatlantic data transfer (EU-US Privacy Shield). (SWP Comments)
Keywords: 320